Invasive rodents and damages to food stocks: a study in the Autonomous Harbor of Cotonou, Benin - (:unkn) unknown (My University, 2020)
Description of the subject. Rodents may be major pests to crops and stored food, thus threatening food security. Among them, invasive species such as rats and mice are of particular concern since they are disseminated globally following international trade. We investigated the small mammal assemblage within the international seaport of Cotonou, Benin, in order to determine the relative importance and distribution of native vs invasive rodent species, as well as to evaluate the amount and associated costs of rodent-induced damages on imported 'exported stored goods (here, rice).Objectives. Description of rodent assemblages within an African seaport, and evaluation of the associated damages on stored food stocks.Method. Rodent communities were described following trapping results while associated damages and costs were evaluated following a 25 days-long monitoring campaign and subsequent economic estimation of loss.Results. Our results show that invasive mice and rats are, from far, the most impacting rodents in the storage warehouses, and that the associated economic losses are quite large. Moreover, we point towards a few environmental management procedures that may greatly reduce the impact of rodents on stored goods.Conclusions. Damages and costs due to invasive rodents within the Cotonou Harbor are so that they justify financial investment in rodent population control.
Keywords: African Research